Land and Building Tax Socialization in the Community of Arcawinangun Village RT 03/ RW 07, East Purwokerto District, Banyumas Regency - Rachmi Fitrijati, Krishnoe; Bakhtiar, Syamsul; Viviyanti, Hanny; Bachtiar, Haris; Ardiansyah, Abid; Sari, Winahyu Febrika (PT FORMOSA CENDEKIA GLOBAL, 2024)
the Arcawinangun Sub-district, East Purwokerto District, Banyumas Regency for Land and Building Tax Socialization, to improve awareness of the community. The program interacted directly with the social capital approach with the community to determine tax understanding and compliance through observation, interview, and socialization stages. The results of community service activities include providing education on the benefits of tax payments, Land and Building Tax levy rates, and payment procedures, as well as solving tax problems that occur in the local community.